Broadband heat-conducting wave-absorbing material and preparation method thereof
By cross-linking and coating carbon nanotubes and silicon carbide and amino modification, combined with vinyl silicone oil and other materials, broadband thermally conductive and wave-absorbing materials are prepared, which solves the problems of taking into account both thermal and wave-absorbing properties in the prior art, and achieves efficient Heat transfer and wide frequency wave absorption performance.
Patent Information
- Application Number
- CN202411444612.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-16
- Publication Date
- 2024-12-27
AI Technical Summary
Existing wave absorbing materials are difficult to take into account excellent thermal conductivity and wave absorbing performance, and usually sacrifice the performance of the other when improving one.
The carbon nanotubes/silicon carbide are comodified by silane coupling agent KH-560, and the cross-linking coating of zero-dimensional filler to one-dimensional filler is achieved by using amine cross-linking agent. Then, carbonyl iron powder is used as the basis for modification The surface graft of the in-situ polymerization-alkane isocyanate of amino-modified-pyrrole was prepared to prepare functional fillers, and combined with vinyl silicone oil, hydrogen-containing silicone oil, catalyst and inhibitor, it was vulcanized into sheets to form a thermally conductive and wave absorbing material.
It achieves excellent thermal conductivity and wave absorption performance over a wide absorbing frequency range, while reducing reflectivity and improving the thermal conductivity and wave absorption effect of the material.
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of wave absorbing materials, and in particular relates to a broadband heat-conducting wave absorbing material and a preparation method thereof. Background Art
[0002] Absorbing materials refer to a type of material that can absorb or significantly reduce the electromagnetic wave energy received on its surface, thereby reducing the interference of electromagnetic waves. They are generally composed of an organic polymer matrix and an inorganic filler medium. In recent years, with the continuous development of science and technology, electronic devices have become more refined and dense, which puts forward higher performance requirements for absorbing materials. Since electronic devices will inevitably generate a lot of heat in addition to electromagnetic radiation (electromagnetic waves) during actual operation, there is no doubt that long-term heat accumulation can easily cause the performance of electronic devices to deteriorate. For this reason, many existing technologies strive to give absorbing materials excellent thermal conductivity. However, these existing technologies often sacrifice some absorbing performance at the expense of the two, and it is difficult to effectively take both into account. A large number of studies have shown that excellent thermal conductivity requires good internal continuity of the material, which can form a thermal conductive path between many thermal conductive fillers, thereby facilitating heat transfer and improving thermal conductivity. Excellent absorbing performance is just the opposite. It requires high dispersion of absorbing fillers to reduce contact between each other in order to broaden the range of absorbing frequencies. Summary of the invention
[0003] In view of the problems existing in the prior art, the purpose of the present invention is to provide a broadband thermal conductive wave absorbing material and a preparation method thereof. The present invention uses a silane coupling agent KH-560 to co-modify carbon nanotubes / one-dimensional fillers and silicon carbide / zero-dimensional fillers, and modifies epoxy groups at the same time, and then adds an amine crosslinking agent. Based on the effect of epoxy-amino groups, the zero-dimensional filler is cross-linked and coated with the one-dimensional filler, thereby preparing a functional filler A. Then, using carbonyl iron powder as a modification basis, the silane coupling agent KH-540 amino modification-pyrrole in-situ polymerization-alkane isocyanate surface grafting are sequentially performed to prepare a functional filler B. When the functional filler A, the functional filler B, vinyl silicone oil, hydrogen-containing silicone oil, a catalyst and an inhibitor are mixed and vulcanized into sheets, a thermal conductive wave absorbing material is obtained, which not only has excellent thermal conductivity, but also has low reflectivity in a wider wave absorbing frequency range and good wave absorbing performance.
[0004] The purpose of the present invention can be achieved by the following technical solutions:
[0005] A broadband heat-conducting and wave-absorbing material is prepared from 100 parts by weight of vinyl silicone oil, 8-10 parts by weight of hydrogen-containing silicone oil, 0.1-1 parts by weight of a catalyst, 0.01-0.03 parts by weight of an inhibitor, 50-70 parts by weight of a functional filler A and 60-80 parts by weight of a functional filler B; the thickness of the heat-conducting and wave-absorbing material is 1-2 mm.
[0006] As a preferred technical solution of the present invention, the viscosity of the vinyl silicone oil is 100-1000 mPa·s at 25°C.
[0007] As a preferred technical solution of the present invention, the hydrogen-containing silicone oil is polymethyl hydrogen siloxane; the viscosity of the polymethyl hydrogen siloxane is 30 mm at 25°C. 2 / s.
[0008] As a preferred technical solution of the present invention, the catalyst is a Custer platinum catalyst; the platinum content of the Custer platinum catalyst is 2000-3000ppm.
[0009] As a preferred technical solution of the present invention, the inhibitor is at least one of 3,5-dimethyl-1-hexyn-3-ol and ethynylcyclohexanol.
[0010] As a preferred technical solution of the present invention, the functional filler A is prepared by the following steps:
[0011] Step X1: adding 100-120 parts by weight of toluene and 1 part by weight of silane coupling agent KH-560 to 2-3 parts by weight of the composite filler, stirring the mixture at 90-100° C. for 8-10 hours in ultrasound, filtering the mixture, taking the residue, washing the residue with acetone, and finally drying the residue under vacuum at 60-80° C. until constant weight is obtained to obtain component A;
[0012] Step X2: add 100-120 parts by weight of dimethyl sulfoxide to the component A, and then add dropwise 1-1.5 parts by weight of an amine crosslinking agent while stirring at 70-80° C. in ultrasound. After the addition is completed, continue to stir at a constant temperature for 4-6 hours, filter, take the filter residue, wash it with deionized water, and finally vacuum dry it at 60-80° C. until constant weight, and the preparation is completed.
[0013] Furthermore, the composite filler in step X1 includes 1-2 parts by weight of a one-dimensional filler and 2 parts by weight of a zero-dimensional filler; the one-dimensional filler is carbon nanotubes; and the zero-dimensional filler is silicon carbide.
[0014] Furthermore, the power of the ultrasound in step X1 is 300-500W.
[0015] Furthermore, the power of the ultrasound in step X2 is 300-500W.
[0016] Furthermore, the dripping rate in step X2 is controlled at 1-3 drops / s.
[0017] Furthermore, the amine cross-linking agent in step X2 is ethylenediamine.
[0018] As a preferred technical solution of the present invention, the functional filler B is prepared by the following steps:
[0019] Step Y1: Add 100-120 parts by weight of anhydrous ethanol and 5 parts by weight of deionized water to 2-3 parts by weight of carbonyl iron powder, and then stir at room temperature for 5-10 minutes, then add 1.5 parts by weight of silane coupling agent KH-540, stir at 70-75° C. for 6-8 hours in ultrasound, filter, take the filter residue, wash with deionized water, and finally vacuum dry at 60-80° C. until constant weight, to obtain component B;
[0020] Step Y2: add 140-150 parts by weight of deionized water, 50 parts by weight of anhydrous ethanol and 6-8 parts by weight of anhydrous ferric chloride to the component B, then stir and mix at room temperature for 5-10 minutes, cool to 2-4°C and keep warm, then dropwise add 3-4 parts by weight of pyrrole while stirring, continue to stir at a constant temperature for 6-8 hours after the dropwise addition is completed, let stand for 15-30 minutes, filter, take the filter residue, wash with deionized water, and finally vacuum dry at 60-80°C until constant weight, to obtain component C;
[0021] Step Y3: Add 100-120 parts by weight of toluene to the component C, and then stir at room temperature for 5-10 minutes to mix, then add dropwise 1.5 parts by weight of alkane isocyanate while stirring at 100-105°C in a nitrogen atmosphere and ultrasound, and continue stirring at a constant temperature for 14-16 hours after the addition is completed, filter, take the filter residue, wash it with deionized water, and finally vacuum dry it at 60-80°C until constant weight, and the preparation is completed.
[0022] Furthermore, the power of the ultrasound in step Y1 is 300-500W.
[0023] Furthermore, the dripping rate in step Y2 is controlled at 1-2 drops / s.
[0024] Furthermore, the power of the ultrasound in step Y3 is 300-500W.
[0025] Furthermore, the dripping rate in step Y3 is controlled at 2-4 drops / s.
[0026] Furthermore, the alkane isocyanate in step Y3 is at least one of tetradecyl isocyanate, hexadecyl isocyanate and octadecyl isocyanate.
[0027] A method for preparing a broadband thermal conductive wave absorbing material, the method comprising the following steps:
[0028] Step A: Stir the vinyl silicone oil, hydrogenated silicone oil, inhibitor, functional filler A and functional filler B at a speed of 1500-2000 rpm for 3-5 minutes, then add the catalyst, continue stirring at a constant speed for 1-3 minutes, and vulcanize into sheets.
[0029] As a preferred technical solution of the present invention, the vulcanization into sheets in step A refers to vulcanization for 1 hour at a temperature of 150-160° C. and a pressure of 5-10 MPa.
[0030] Beneficial effects of the present invention:
[0031] (1) The present invention utilizes silane coupling agent KH-560 to co-modify carbon nanotube / one-dimensional filler and silicon carbide / zero-dimensional filler, and modifies epoxy groups at the same time, and then adds an amine crosslinking agent. Based on the effect of epoxy-amino group, the zero-dimensional filler is cross-linked and coated on the one-dimensional filler, thereby preparing functional filler A. Then, carbonyl iron powder is used as the modification basis, and the silane coupling agent KH-540 amino modification-pyrrole in-situ polymerization-alkane isocyanate surface grafting are sequentially performed to prepare functional filler B. When functional filler A, functional filler B, vinyl silicone oil, hydrogen-containing silicone oil, catalyst and inhibitor are mixed and vulcanized into sheets, a thermal conductive wave absorbing material is obtained, which not only has excellent thermal conductivity, but also has low reflectivity in a wide wave absorbing frequency range and good wave absorbing performance.
[0032] (2) The present invention creatively selects carbon nanotubes as one-dimensional fillers and silicon carbide as zero-dimensional fillers, and crosslinks and coats one-dimensional fillers with high aspect ratio characteristics through zero-dimensional fillers, thereby preparing functional filler A, which mainly plays an excellent thermal conductivity role in thermal conductive and absorbing materials. Compared with the prior art that simply mixes the two, the crosslinking and coating treatment of the present invention can construct a large number of thermal conductive paths in advance, promote the contact between thermal conductive fillers, thereby facilitating heat transfer and improving thermal conductivity. In addition, the present invention is based on an in-situ polymerization method, in which a carbonyl iron modified with an amino group is used. Polypyrrole is polymerized on the surface of the powder to achieve the synergistic combination of the two loss mechanisms of magnetic loss and dielectric loss, thereby obtaining better impedance matching and promoting the wave absorption effect. At the same time, alkane isocyanate with a certain number of carbon atoms is used to further modify the polypyrrole through the action of imino and isocyanate groups to form a structure with long-chain alkanes facing outward. From a microscopic point of view, long-chain alkanes with a certain number of carbon atoms can reduce the interface contact with other fillers through their own steric effect, promote interface separation, and obtain better dispersion effect. Correspondingly, the range of wave absorption frequency can be widened and the wave absorption performance can be enhanced.
[0033] (3) The present invention rationally designs and coordinates the functional filler A and the functional filler B so that they together endow the thermal conductive and wave absorbing material with excellent thermal conductivity and wave absorbing performance. DETAILED DESCRIPTION
[0034] In order to further illustrate the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, the specific implementation methods, structures, features and effects of the present invention are described in detail below in combination with the embodiments.
[0035] The carbon nanotubes in all the embodiments and comparative examples of the present invention were purchased directly from the market, purchased from Jiangsu Xianfeng Nanomaterial Technology Co., Ltd., and the product number was XFM13; the silicon carbide was purchased directly from the market, purchased from Shanghai Pantian Powder Material Co., Ltd., and the product number was PT-Si C-800nm; the carbonyl iron powder was purchased directly from the market, purchased from Zhongke Yannuo (Beijing) Technology Co., Ltd., and the product number was BM11698; the vinyl silicone oil was purchased directly from the market, purchased from Anhui Mingyi Silicon Industry Co., Ltd., the model was MY 273 vinyl silicone oil, and the viscosity was 500 mPa·s at 25°C.
[0036] The heat-conductive and wave-absorbing materials prepared in all the embodiments and comparative examples of the present invention are in the shape of a cuboid, and both the length and width are 300 mm.
[0037] Example 1
[0038] A broadband heat-conducting and wave-absorbing material is prepared from 100 parts by weight of vinyl silicone oil, 8 parts by weight of hydrogen-containing silicone oil, 0.1 parts by weight of a catalyst, 0.01 parts by weight of an inhibitor, 50 parts by weight of a functional filler A, and 60 parts by weight of a functional filler B; the thickness of the heat-conducting and wave-absorbing material is 1 mm.
[0039] The hydrogen-containing silicone oil is polymethyl hydrogen siloxane; the viscosity of the polymethyl hydrogen siloxane is 30 mm at 25°C. 2 / s.
[0040] The catalyst is a Custer platinum catalyst; the platinum content of the Custer platinum catalyst is 2000ppm.
[0041] The inhibitor is 3,5-dimethyl-1-hexyn-3-ol.
[0042] The functional filler A is prepared by the following steps:
[0043] Step X1: adding 100 parts by weight of toluene and 1 part by weight of silane coupling agent KH-560 to 2 parts by weight of the composite filler, stirring the mixture at 90° C. for 8 hours in ultrasound, filtering the mixture, taking the residue, washing the residue with acetone, and finally drying the mixture under vacuum at 60° C. until the weight is constant, thereby obtaining component A;
[0044] Step X2: add 100 parts by weight of dimethyl sulfoxide to the component A, and then add dropwise 1 part by weight of ethylenediamine while stirring at 70°C in ultrasound. After the addition is completed, continue stirring at a constant temperature for 4 hours, filter, take the filter residue, wash it with deionized water, and finally vacuum dry it at 60°C until constant weight, and the preparation is completed.
[0045] The composite filler in step X1 includes 1 part by weight of a one-dimensional filler and 2 parts by weight of a zero-dimensional filler; the one-dimensional filler is carbon nanotubes; and the zero-dimensional filler is silicon carbide.
[0046] The power of the ultrasound in step X1 is 300W.
[0047] The power of the ultrasound in step X2 is 300W.
[0048] The dripping rate in step X2 is controlled at 1 drop / s.
[0049] The functional filler B is prepared by the following steps:
[0050] Step Y1: Add 100 parts by weight of anhydrous ethanol and 5 parts by weight of deionized water to 2 parts by weight of carbonyl iron powder, and then stir and mix at room temperature for 5 minutes, then add 1.5 parts by weight of silane coupling agent KH-540, stir at 70° C. for 6 hours in ultrasound, filter, take the filter residue, wash with deionized water, and finally vacuum dry at 60° C. until constant weight, to obtain component B;
[0051] Step Y2: add 140 parts by weight of deionized water, 50 parts by weight of anhydrous ethanol and 6 parts by weight of anhydrous ferric chloride to the component B, then stir and mix at room temperature for 5 minutes, cool to 2°C and keep warm, then dropwise add 3 parts by weight of pyrrole while stirring, continue to stir at a constant temperature for 6 hours after the dropwise addition is completed, let stand for 15 minutes, filter, take the filter residue, wash with deionized water, and finally vacuum dry at 60°C until constant weight, to obtain component C;
[0052] Step Y3: Add 100 parts by weight of toluene to the component C, and then stir at room temperature for 5 minutes to mix, then add 1.5 parts by weight of hexadecyl isocyanate dropwise while stirring at 100°C in a nitrogen atmosphere and ultrasound, and continue stirring at a constant temperature for 14 hours after the addition is completed, filter, take the filter residue, wash it with deionized water, and finally vacuum dry it at 60°C until constant weight, and the preparation is completed.
[0053] The power of the ultrasound in step Y1 is 300W.
[0054] The dripping rate in step Y2 is controlled at 1 drop / s.
[0055] The power of the ultrasound in step Y3 is 300W.
[0056] The dripping rate in step Y3 is controlled at 2 drops / s.
[0057] A method for preparing a broadband thermal conductive wave absorbing material, the method comprising the following steps:
[0058] Step A: Stir vinyl silicone oil, hydrogen silicone oil, inhibitor, functional filler A and functional filler B at a speed of 1500 rpm for 3 minutes, then add the catalyst, continue to stir at a constant speed for 1 minute, and vulcanize into sheets.
[0059] The vulcanization into sheets in step A refers to vulcanization for 1 hour at a temperature of 150° C. and a pressure of 5 MPa.
[0060] Example 2
[0061] A broadband heat-conducting and wave-absorbing material is prepared from 100 parts by weight of vinyl silicone oil, 10 parts by weight of hydrogenated silicone oil, 1 part by weight of a catalyst, 0.03 parts by weight of an inhibitor, 70 parts by weight of a functional filler A, and 80 parts by weight of a functional filler B; the thickness of the heat-conducting and wave-absorbing material is 2 mm.
[0062] The hydrogen-containing silicone oil is polymethyl hydrogen siloxane; the viscosity of the polymethyl hydrogen siloxane is 30 mm at 25°C. 2 / s.
[0063] The catalyst is a Custer platinum catalyst; the platinum content of the Custer platinum catalyst is 3000 ppm.
[0064] The inhibitor is 3,5-dimethyl-1-hexyn-3-ol.
[0065] The functional filler A is prepared by the following steps:
[0066] Step X1: adding 120 parts by weight of toluene and 1 part by weight of silane coupling agent KH-560 to 3 parts by weight of the composite filler, stirring the mixture at 100° C. for 10 hours in ultrasound, filtering the mixture, taking the filter residue, washing the residue with acetone, and finally drying the mixture under vacuum at 80° C. until the weight is constant, thereby obtaining component A;
[0067] Step X2: Add 120 parts by weight of dimethyl sulfoxide to the component A, and then dropwise add 1.5 parts by weight of ethylenediamine while stirring at 80°C in ultrasound. After the dropwise addition is completed, continue to stir at a constant temperature for 6 hours, filter, take the filter residue, wash it with deionized water, and finally vacuum dry it at 80°C until constant weight, and the preparation is completed.
[0068] The composite filler in step X1 includes 2 parts by weight of a one-dimensional filler and 2 parts by weight of a zero-dimensional filler; the one-dimensional filler is carbon nanotubes; and the zero-dimensional filler is silicon carbide.
[0069] The power of the ultrasound in step X1 is 500W.
[0070] The power of the ultrasound in step X2 is 500W.
[0071] The dropping rate in step X2 is controlled at 3 drops / s.
[0072] The functional filler B is prepared by the following steps:
[0073] Step Y1: Add 120 parts by weight of anhydrous ethanol and 5 parts by weight of deionized water to 3 parts by weight of carbonyl iron powder, and then stir and mix at room temperature for 10 minutes, then add 1.5 parts by weight of silane coupling agent KH-540, stir at 75° C. for 8 hours in ultrasound, filter, take the filter residue, wash with deionized water, and finally vacuum dry at 80° C. until constant weight, to obtain component B;
[0074] Step Y2: add 150 parts by weight of deionized water, 50 parts by weight of anhydrous ethanol and 8 parts by weight of anhydrous ferric chloride to the component B, then stir and mix at room temperature for 10 minutes, cool to 4°C and keep warm, then dropwise add 4 parts by weight of pyrrole while stirring, continue to stir at a constant temperature for 8 hours after the dropwise addition is completed, let stand for 30 minutes, filter, take the filter residue, wash with deionized water, and finally vacuum dry at 80°C until constant weight, to obtain component C;
[0075] Step Y3: Add 120 parts by weight of toluene to the component C, and then stir and mix at room temperature for 10 minutes, then dropwise add 1.5 parts by weight of hexadecyl isocyanate while stirring at 105°C in a nitrogen atmosphere and ultrasound, and continue stirring at a constant temperature for 16 hours after the addition is completed, filter, take the filter residue, wash it with deionized water, and finally vacuum dry it at 80°C until constant weight, and the preparation is completed.
[0076] The power of the ultrasound in step Y1 is 500W.
[0077] The dripping rate in step Y2 is controlled at 2 drops / s.
[0078] The power of the ultrasound in step Y3 is 500W.
[0079] The dripping rate in step Y3 is controlled at 4 drops / s.
[0080] A method for preparing a broadband thermal conductive wave absorbing material, the method comprising the following steps:
[0081] Step A: Vinyl silicone oil, hydrogenated silicone oil, inhibitor, functional filler A and functional filler B are stirred at a speed of 2000 rpm for 5 minutes, then a catalyst is added, stirring is continued at a constant speed for 3 minutes, and vulcanized into sheets.
[0082] The vulcanization into sheets in step A refers to vulcanization for 1 hour at a temperature of 160° C. and a pressure of 10 MPa.
[0083] Example 3
[0084] A broadband heat-conducting and wave-absorbing material is prepared from 100 parts by weight of vinyl silicone oil, 9 parts by weight of hydrogen-containing silicone oil, 0.5 parts by weight of a catalyst, 0.02 parts by weight of an inhibitor, 60 parts by weight of a functional filler A, and 70 parts by weight of a functional filler B; the thickness of the heat-conducting and wave-absorbing material is 1.5 mm.
[0085] The hydrogen-containing silicone oil is polymethyl hydrogen siloxane; the viscosity of the polymethyl hydrogen siloxane is 30 mm at 25°C. 2 / s.
[0086] The catalyst is a Custer platinum catalyst; the platinum content of the Custer platinum catalyst is 2500ppm.
[0087] The inhibitor is 3,5-dimethyl-1-hexyn-3-ol.
[0088] The functional filler A is prepared by the following steps:
[0089] Step X1: adding 110 parts by weight of toluene and 1 part by weight of silane coupling agent KH-560 to 2.5 parts by weight of the composite filler, stirring at 95° C. for 9 hours in ultrasound, filtering, taking the filter residue, washing with acetone, and finally vacuum drying at 70° C. until constant weight, to obtain component A;
[0090] Step X2: Add 110 parts by weight of dimethyl sulfoxide to the component A, and then dropwise add 1.3 parts by weight of ethylenediamine while stirring at 75°C in ultrasound. After the dropwise addition is completed, continue to stir at a constant temperature for 5 hours, filter, take the filter residue, wash it with deionized water, and finally vacuum dry it at 70°C until constant weight, and the preparation is completed.
[0091] The composite filler in step X1 includes 1.5 parts by weight of a one-dimensional filler and 2 parts by weight of a zero-dimensional filler; the one-dimensional filler is carbon nanotubes; and the zero-dimensional filler is silicon carbide.
[0092] The power of the ultrasound in step X1 is 400W.
[0093] The power of the ultrasound in step X2 is 400W.
[0094] The dripping rate in step X2 is controlled at 2 drops / s.
[0095] The functional filler B is prepared by the following steps:
[0096] Step Y1: Add 110 parts by weight of anhydrous ethanol and 5 parts by weight of deionized water to 2.5 parts by weight of carbonyl iron powder, and then stir and mix at room temperature for 8 minutes, then add 1.5 parts by weight of silane coupling agent KH-540, stir at 73° C. for 7 hours in ultrasound, filter, take the filter residue, wash with deionized water, and finally vacuum dry at 70° C. until constant weight, to obtain component B;
[0097] Step Y2: add 145 parts by weight of deionized water, 50 parts by weight of anhydrous ethanol and 7 parts by weight of anhydrous ferric chloride to the component B, then stir and mix at room temperature for 8 minutes, cool to 3°C and keep warm, then dropwise add 3.5 parts by weight of pyrrole while stirring, continue to stir at a constant temperature for 7 hours after the dropwise addition is completed, let stand for 20 minutes, filter, take the filter residue, wash with deionized water, and finally vacuum dry at 70°C until constant weight, to obtain component C;
[0098] Step Y3: Add 110 parts by weight of toluene to the component C, and then stir and mix at room temperature for 8 minutes, then dropwise add 1.5 parts by weight of hexadecyl isocyanate while stirring at 103°C in a nitrogen atmosphere and ultrasound, and continue stirring at a constant temperature for 15 hours after the addition is completed, filter, take the filter residue, wash it with deionized water, and finally vacuum dry it at 70°C until constant weight, and the preparation is completed.
[0099] The power of the ultrasound in step Y1 is 400W.
[0100] The dripping rate in step Y2 is controlled at 1.5 drops / s.
[0101] The power of the ultrasound in step Y3 is 400W.
[0102] The dripping rate in step Y3 is controlled at 3 drops / s.
[0103] A method for preparing a broadband thermal conductive wave absorbing material, the method comprising the following steps:
[0104] Step A: Vinyl silicone oil, hydrogenated silicone oil, inhibitor, functional filler A and functional filler B are stirred at a speed of 1800 rpm for 4 minutes, then a catalyst is added, stirring is continued at a constant speed for 2 minutes, and vulcanized into sheets.
[0105] The vulcanization into sheets in step A refers to vulcanization for 1 hour at a temperature of 155° C. and a pressure of 8 MPa.
[0106] Comparative Example 1
[0107] On the basis of Example 1, the silane coupling agent KH-560 in step X1 was replaced by an equal weight of deionized water, and the ethylenediamine in step X2 was replaced by an equal weight of deionized water, and the rest remained unchanged.
[0108] Comparative Example 2
[0109] On the basis of Example 1, the functional filler B was replaced by an equal weight of carbonyl iron powder, and the rest remained unchanged.
[0110] Comparative Example 3
[0111] On the basis of Example 1, step Y3 is not performed and the rest remain unchanged.
[0112] Test Example 1
[0113] Thermal conductivity test:
[0114] The thermal conductivity of the heat-conductive and wave-absorbing materials prepared in Examples 1-3 and Comparative Examples 1-3 was tested according to standard AST M D5470.
[0115] Table 1. Thermal conductivity test results
[0116] <![CDATA[Thermal conductivity / (W·m -1 ·K -1 )]]> Example 1 3.9 Example 2 4.5 Example 3 4.2 Comparative Example 1 2.5 Comparative Example 2 4.1 Comparative Example 3 3.9
[0117] Test Example 2
[0118] Wave absorption performance test:
[0119] The heat-conductive wave-absorbing materials prepared in Examples 1-3 and Comparative Examples 1-3 were respectively tested for wave-absorbing performance using the GJB2038A-2011 bow method, and the reflectivity in the frequency range of 1 GHz to 40 GHz was statistically determined to be less than -5 dB.
[0120] Table 2. Wave absorption performance test results
[0121] Reflectivity Example 1 yes Example 2 yes Example 3 yes Comparative Example 1 no Comparative Example 2 no Comparative Example 3 no
[0122] From the comparison between Test Examples 1-2, Example 1 and Comparative Examples 1-3, it can be seen that only the thermal conductive and absorbing material prepared by the present invention not only has a thermal conductivity above 3 W·m-1·K-1, but also has a reflectivity value less than -5 dB in a wide frequency range of 1 GHz-40 GHz.
[0123] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technical personnel in this field can make some changes or modify the technical contents disclosed above into equivalent embodiments without departing from the scope of the technical solution of the present invention. However, any brief modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention are still within the scope of the technical solution of the present invention.
Claims
1. A broadband heat-conducting and wave-absorbing material, characterized in that: The thermal conductive wave absorbing material is prepared from 100 parts by weight of vinyl silicone oil, 8-10 parts by weight of hydrogenated silicone oil, 0.1-1 parts by weight of a catalyst, 0.01-0.03 parts by weight of an inhibitor, 50-70 parts by weight of a functional filler A and 60-80 parts by weight of a functional filler B; the thickness of the thermal conductive wave absorbing material is 1-2 mm.
2. A broadband heat-conducting and wave-absorbing material according to claim 1, characterized in that: The viscosity of the vinyl silicone oil is 100-1000 mPa·s at 25°C.
3. The broadband heat-conducting and wave-absorbing material according to claim 1, characterized in that: The hydrogen-containing silicone oil is polymethyl hydrogen siloxane; the viscosity of the polymethyl hydrogen siloxane is 30 mm at 25°C. 2 / s.
4. The broadband heat-conducting and wave-absorbing material according to claim 1, characterized in that: The catalyst is a Custer platinum catalyst; the platinum content of the Custer platinum catalyst is 2000-3000ppm.
5. The broadband heat-conducting and wave-absorbing material according to claim 1, characterized in that: The functional filler A is prepared by the following steps: Step X1: adding 100-120 parts by weight of toluene and 1 part by weight of silane coupling agent KH-560 to 2-3 parts by weight of the composite filler, stirring the mixture at 90-100° C. for 8-10 hours in ultrasound, filtering the mixture, taking the residue, washing the residue with acetone, and finally drying the residue under vacuum at 60-80° C. until constant weight is obtained to obtain component A; Step X2: add 100-120 parts by weight of dimethyl sulfoxide to the component A, and then add dropwise 1-1.5 parts by weight of an amine crosslinking agent while stirring at 70-80° C. in ultrasound. After the addition is completed, continue to stir at a constant temperature for 4-6 hours, filter, take the filter residue, wash it with deionized water, and finally vacuum dry it at 60-80° C. until constant weight, and the preparation is completed.
6. The broadband heat-conducting and wave-absorbing material according to claim 5, characterized in that: The composite filler in step X1 includes 1-2 parts by weight of a one-dimensional filler and 2 parts by weight of a zero-dimensional filler; the one-dimensional filler is carbon nanotubes; and the zero-dimensional filler is silicon carbide.
7. The broadband heat-conducting and wave-absorbing material according to claim 5, characterized in that: The amine cross-linking agent in step X2 is ethylenediamine.
8. The broadband heat-conducting and wave-absorbing material according to claim 1, characterized in that: The functional filler B is prepared by the following steps: Step Y1: Add 100-120 parts by weight of anhydrous ethanol and 5 parts by weight of deionized water to 2-3 parts by weight of carbonyl iron powder, and then stir at room temperature for 5-10 minutes, then add 1.5 parts by weight of silane coupling agent KH-540, stir at 70-75° C. for 6-8 hours in ultrasound, filter, take the filter residue, wash with deionized water, and finally vacuum dry at 60-80° C. until constant weight, to obtain component B; Step Y2: add 140-150 parts by weight of deionized water, 50 parts by weight of anhydrous ethanol and 6-8 parts by weight of anhydrous ferric chloride to the component B, then stir and mix at room temperature for 5-10 minutes, cool to 2-4°C and keep warm, then dropwise add 3-4 parts by weight of pyrrole while stirring, continue to stir at a constant temperature for 6-8 hours after the dropwise addition is completed, let stand for 15-30 minutes, filter, take the filter residue, wash with deionized water, and finally vacuum dry at 60-80°C until constant weight, to obtain component C; Step Y3: Add 100-120 parts by weight of toluene to the component C, and then stir at room temperature for 5-10 minutes to mix, then add dropwise 1.5 parts by weight of alkane isocyanate while stirring at 100-105°C in a nitrogen atmosphere and ultrasound, and continue stirring at a constant temperature for 14-16 hours after the addition is completed, filter, take the filter residue, wash it with deionized water, and finally vacuum dry it at 60-80°C until constant weight, and the preparation is completed.
9. The broadband heat-conducting and wave-absorbing material according to claim 8, characterized in that: The alkane isocyanate in step Y3 is at least one of tetradecyl isocyanate, hexadecyl isocyanate and octadecyl isocyanate.
10. A method for preparing a broadband heat-conducting and wave-absorbing material according to any one of claims 1 to 9, characterized in that: The preparation method comprises the following steps: Step A: Stir the vinyl silicone oil, hydrogenated silicone oil, inhibitor, functional filler A and functional filler B at a speed of 1500-2000 rpm for 3-5 minutes, then add the catalyst, continue stirring at a constant speed for 1-3 minutes, and vulcanize into sheets.
